KEPEMIMPINAN KEPALA SEKOLAH ISLAM DALAM PENINGKATAN AKHLAK SISWA SMK - Dario Azhari Syaifuddin; Mohammad Zakki Azani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The background of this study is based on the important role of school principals in fostering students’ moral character in the digital era, which is marked by the strong influence of social media and changes in adolescent behavior. This study aims to describe the leadership style of the principal of Muhammadiyah Vocational High School 5 Karanganyar in improving students’ morals and to identify the strategies, supporting factors, and inhibiting factors involved. The study employed a qualitative approach using a case study design. The research stages included data collection through in-depth interviews with the principal as the main informant, documentation of school programs, and descriptive-interpretative data analysis. The results showed that the principal implemented a democratic-transformational leadership style based on Islamic values emphasizing role modeling, deliberation, and empowerment. The leading strategies included linking viral topics with Islamic values, Friday religious studies with students serving as speakers in rotation, personal approaches through counseling spaces, and the habituation of a religious culture within the school environment. The main supporting factors were the principal’s commitment, support from teachers and parents, and the strong Muhammadiyah culture, while the inhibiting factors included the negative influence of social media and limited school resources. The main conclusion of this study indicates that spiritual-ihsan leadership is effective in creating a conducive school ecosystem for the sustainable development of students’ moral character in the digital era. ABSTRAK Latar belakang penelitian ini didasarkan pada pentingnya peran kepala sekolah dalam membina akhlak siswa di era digital yang ditandai dengan kuatnya pengaruh media sosial dan perubahan perilaku remaja. Penelitian ini bertujuan mendeskripsikan gaya kepemimpinan kepala sekolah SMK Muhammadiyah 5 Karanganyar dalam meningkatkan akhlak siswa serta mengidentifikasi strategi, faktor pendukung, dan faktor penghambatnya. Penelitian menggunakan pendekatan kualitatif dengan jenis studi kasus. Tahapan penelitian meliputi pengumpulan data melalui wawancara mendalam dengan kepala sekolah sebagai informan utama, dokumentasi program sekolah, serta analisis data secara deskriptif interpretatif. Hasil penelitian menunjukkan bahwa kepala sekolah menerapkan gaya kepemimpinan demokratis-transformasional berbasis nilai-nilai Islam yang menekankan keteladanan, musyawarah, dan pemberdayaan. Strategi unggulan yang diterapkan meliputi pengaitan topik viral dengan nilai Islam, kajian Jumat dengan penceramah siswa secara bergiliran, pendekatan personal melalui ruang curhat, serta pembiasaan budaya religius di lingkungan sekolah. Faktor pendukung utama adalah komitmen kepala sekolah, dukungan guru dan orang tua, serta kultur Muhammadiyah yang kuat, sedangkan faktor penghambat meliputi pengaruh negatif media sosial dan keterbatasan sumber daya sekolah. Simpulan utama penelitian ini menunjukkan bahwa kepemimpinan spiritual-ihsan efektif dalam menciptakan ekosistem sekolah yang kondusif bagi pembinaan akhlak siswa secara berkelanjutan di era digital.